Multiple interferences suppression method based on adaptive signal data regrouping for GNSS receivers. Issue 6 (11th April 2018) - Guo, Qiang; Qi, Liangang; Xiang, Jianhong; Ruan, Guoqing
Abstract : The number of wide‐band interfering signals which can be suppressed by an antenna array is limited to the number of antenna elements. To address this problem, a multiple interferences suppression method based on adaptive signal data regrouping for global navigation satellite system (GNSS) receivers is proposed on the basis of analysing the generalised periodic and sparse property of the wide‐band periodic frequency modulated (WBPFM) signals. By exploiting the feature of the singular value ratio (SVR) spectrum of received signals containing periodic components, the authors introduce an improved SVR‐based period estimation method to estimate the minimum common period (MCP) of WBPFM interfering signals. Regroup the signal data to construct space–time (ST) matrixes according to the estimated MCP. Then, an orthogonal minimum power distortionless response‐based ST processor is adopted to nullify the interferences and protect GNSS signals. Simulation results show that the proposed method can suppress more wide‐band interferences without increasing the number of antenna elements.